Improving the development of early bovine somatic‐cell nuclear transfer embryos by treating adult donor cells with vitamin C. Issue 11 (10th August 2015) - Chen, Huanhuan; Zhang, Lei; Guo, Zekun; Wang, Yongsheng; He, Rongjun; Qin, Yumin; Quan, Fusheng; Zhang, Yong
SUMMARY: Vitamin C (Vc) has been widely studied in cell and embryo culture, and has recently been demonstrated to promote cellular reprogramming. The objective of this study was to identify a suitable Vc concentration that, when used to treat adult bovine fibroblasts serving as donor cells for nuclear transfer, improved donor‐cell physiology and the developmental potential of the cloned embryos that the donor nuclei were used to create. A Vc concentration of 0.15 mM promoted cell proliferation and increased donor‐cell 5‐hydroxy methyl cytosine levels 2.73‐fold ( P  < 0.05). The blastocyst rate was also significantly improved after nuclear transfer (39.6% treated vs. 26.0% control, P  < 0.05); the average number of apoptotic cells in cloned blastocysts was significantly reduced (2.2 vs. 4.4, P  < 0.05); and the inner cell mass‐to‐trophectoderm ratio (38.25% vs. 30.75%, P  < 0.05) and expression of SOX2 (3.71‐fold, P  < 0.05) and POU5F1 (3.15‐fold, P  < 0.05) were significantly increased. These results suggested that Vc promotes cell proliferation, decreases DNA methylation levels in donor cells, and improves the developmental competence of bovine somatic‐cell nuclear transfer embryos. Mol. Reprod. Dev. 82: 867–879, 2015. © 2015 Wiley Periodicals, Inc .